LAYANAN BIMBINGAN DAN KONSELING PRIBADI SOSIAL DALAM MENUMBUHKAN SIKAP POSITIF SISWA - Ina Ambar Ambar Wati (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2018)
There are still many students who violate the rules at school making them hampered to achieve success. Not only that, if this is left unchecked, it will make the character of students not good. The purpose of writing this journal is to fnd out the right way so that each student can obey the discipline at school. Where if this can be done surely the system and purpose of an institution will be easily achieved. Personal social guidance and counseling services are an alternative as an effort to make students obey the rules. Counseling services emphasize change in addressing discipline. By changing negative attitudes such as breaking the rules into a positive attitude that is obeying the order. Learners’ positive attitudes toward discipline can be used as an alternative to changing the rules of curbing and burdensome dicipline into something very useful. And can make students carry out their responsibilities from their heart and willingness not because of coercion or fear of blasphemy, because obeying the rules will lead students to success.